Optimalisasi Pemanfaatan Limbah Peternakan Sapi Perah sebagai Upaya Peningkatan Kualitas Lahan Pertanian Berbasis Pertanian Urban - Qomariah, Umi Kulsum Nur; Hidayat, Rohmat; Susanti, Ambar; Ahmidah, Silfi Alfi; Fatiha, Ulan Supartini; Wijayanti, Sri; Ahmad, Dziqi Jamaludin (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
In the context of urban agriculture, the utilization of livestock waste is key to improving the quality of agricultural land. Liquid organic fertilizer is one of the products derived from dairy farm waste and other organic materials. This article discusses a community service program run in Murukan Village, which is the center of dairy farming and has great potential in farm waste management. Although cow's milk is the identity of this village, farm waste that has the potential to be used to improve agriculture is still underutilized. In order to optimize the use of livestock waste, the community service team designed and conducted training with the theme "Optimizing the Utilization of Dairy Farm Waste as an Effort to Improve the Quality of POC-Based Agricultural Land." The objectives of this community service program are: (1) Provide an understanding to the service subjects about the utilization of dairy milk waste as the main media for POC as a support for the quality of agricultural land (2) increase the skills of making POC from dairy milk waste. (3) provide motivation to farmers not to depend on synthetic chemical fertilizers. The Asset Based Communities Development (ABCD) approach is used in this program, which focuses on identifying existing assets in the community to support empowerment efforts. The results of this activity show an increase in the understanding and skills of the local community in pete waste management.